Appropriate level of lactose in a plasma protein-based diet for the early-weaned pig - K Q Owen; L J Kats; Jim L Nelssen; Michael D Tokach; Robert D Goodband; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 1993)
A total of 367 weanling pigs (initially 11.8 lb and 21 d of age) was used in a 28 d growth assay to determine the appropriate level of lactose needed in phase I diets containing spray-dried porcine plasma (SDPP) for the early-weaned pig. Pigs were blocked by weight and randomly assigned to one of six experimental diets: a positive control or five diets calculated to contain 7, 11, 15, 19, or 23% lactose. The positive control was a high nutrient density diet (HNDD) containing 7.5% SDPP, 1.75% spray-dried blood meal (SDBM), and 20% edible grade dried whey. The five lactose diets were achieved by adding lactose to a common basal diet containing 10% edible grade dried whey, 7.5% SDPP, and 1.75% SDBM. Because whey contains approximately 72% lactose, total lactose levels of 7, 11, 15, 19, or 23% were achieved by not adding any or adding 4, 8, 12, or 16% lactose, respectively, to the basal diet. All diets contained 1.5% lysine, .9% calcium and .8% phosphorus. Pigs were fed pelleted diets from d 0 to 14 postweaning. On d 14, all pigs were switched to a common phase II diet containing 10% edible grade dried whey and 2.5% SDBM and formulated to contain 1.25% lysine. Pigs were fed this diet in a meal form for the remainder of the trial (d 14 to 28 postweaning). A linear response occurred for average daily gain (ADG), average daily feed intake (ADFI), and feed efficiency (F/G) during phase I, with pigs receiving the diet containing the highest level of lactose (23%) having the greatest growth performance. Pigs receiving the diet containing the highest level of lactose also had better daily gains and daily feed intakes when compared to pigs receiving the positive control diet. However, feed efficiency was similar between these two treatments. During phase II, no differences occurred in ADG and F/G, but a linear increase was observed for daily feed intake. Over the total trial, a linear improvement was observed in all performance criteria (ADG, ADFI, and F/G) with increasing dietary lactose. Furthermore, pigs consuming the highest level of lactose had higher daily gain and consumed more feed per day when compared to pigs offered the positive control diet. Results from this research indicate that starter pig performance is improved linearly as lactose levels increase from 7 to 23% in a phase I nursery diet.; Swine Day, Manhattan, KS, November 18,1993
Keywords: Swine day; 1993; Kansas Agricultural Experiment Station contribution; no. 94-194-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 695; Swine; Lactose; Starter pigs; Performance